The first 100 thrombolysis cases in a novel Scottish mesh telestroke system. Issue 4 (November 2013) - Hill, E; Whitehead, M; MacInnes, B; Ellis, G; Talbot, A; Brodie, F; Hughes, N; Beggs, S; Barber, M
Stroke thrombolysis has been a major driver for change within stroke services. However, until recently its widespread application has been limited to tertiary centres. Transfer to tertiary care can lead to significant delays in thrombolysis. We developed a novel mesh telestroke network, which allows stroke specialists to make videoconference-based thrombolysis decisions either from one of three stroke units or from home. We report data on the first 100 patients treated using this model and retrospectively review the first 100 strokes thrombolysed with tissue plasminogen activator across three stroke units. Prospectively collected data were extracted from the Stroke Audit In Lanarkshire database. Case notes were retrieved for clarification when necessary. Outcome measures were timings from symptom onset to infusion, post-thrombolysis symptomatic intracerebral haemorrhage and death. Fifty-one percent of cases were assessed by telestroke link. Median symptom onset to thrombolysis was 160 min (IQR 125–190). There were two symptomatic intracerebral haemorrhages, both in patients assessed face-to-face. Overall mortality was 14%. Our experience of tissue plasminogen activator is comparable to UK data extracted from SITS-MOST in overall timings and complication rates. This model of telemedicine could be replicated to provide safe thrombolysis to areas with challenging infrastructure, geography or insufficient stroke specialist cover.